Caerin 1.1 and 1.9 peptides induce acute caspase 3/GSDME-mediated pyroptosis in epithelial cancer cells - Yuandong Luo; Junjie Li; Quanlan Fu; Pingping Zhang; Xinyi Song; Mengqi Liu; Rongmi Mo; Jiawei Fu; Shuxian Tang; Jialing Wu; Xiaodan Yang; Xiaosong Liu; et al. (Scientific Reports)
Abstract Caerin peptides exhibit a dual role in cancer treatment by directly killing cancer cells and modulating the tumour microenvironment to enhance anti-tumour immunity. This study investigates the mechanisms underlying caerin 1.1/1.9-induced acute cell death in epithelial cancer cells and explores their therapeutic potential. HeLa, A549, and Huh-7 cancer cell lines were treated with caerin 1.1/1.9 peptides. Morphological observations, flow cytometry, lactate dehydrogenase (LDH) release, and IL-18 secretion assays revealed the occurrence of pyroptosis following treatment. Specifically, a 1-h treatment with caerin 1.1/1.9 induced pyroptosis in HeLa, A549, and Huh-7 cells, characterised by cell swelling, membrane bubbling, and the release of IL-18 and LDH. Western blotting confirmed the upregulation of pyroptosis markers, including caspase-3, cleaved caspase-3, and GSDME-N fragments. These findings highlight the significant role of caerin peptides in inducing acute pyroptosis, a form of programmed cell death that enhances the immunogenicity of dying cancer cells, thus potentially improving the effectiveness of immunotherapies. This research underscores the therapeutic potential of caerin 1.1/1.9 peptides in cancer treatment, providing a foundation for developing new anti-cancer strategies that leverage both direct cytotoxic effects and immune modulation to achieve more effective and sustained anti-tumour responses.